Comprehensive analysis of SARS‐CoV‐2 antibody dynamics in New Zealand. Issue 3 (14th March 2021) - Whitcombe, Alana L; McGregor, Reuben; Craigie, Alyson; James, Alex; Charlewood, Richard; Lorenz, Natalie; Dickson, James MJ; Sheen, Campbell R; Koch, Barbara; Fox‐Lewis, Shivani; McAuliffe, Gary; Roberts, Sally A; et al.
Abstract: Objectives: Circulating antibodies are important markers of previous infection and immunity. Questions remain with respect to the durability and functionality of SARS‐CoV‐2 antibodies. This study explored antibody responses in recovered COVID‐19 patients in a setting where the probability of re‐exposure is effectively nil, owing to New Zealand's successful elimination strategy. Methods: A triplex bead‐based assay that detects antibody isotype (IgG, IgM and IgA) and subclass (IgG1, IgG2, IgG3 and IgG4) responses against Nucleocapsid (N) protein, the receptor binding domain (RBD) and Spike (S) protein of SARS‐CoV‐2 was developed. After establishing baseline levels with pre‐pandemic control sera ( n = 113), samples from PCR‐confirmed COVID‐19 patients with mild–moderate disease ( n = 189) collected up to 8 months post‐infection were examined. The relationship between antigen‐specific antibodies and neutralising antibodies (NAbs) was explored with a surrogate neutralisation assay that quantifies inhibition of the RBD/hACE‐2 interaction. Results: While most individuals had broad isotype and subclass responses to each antigen shortly after infection, only RBD and S protein IgG, as well as NAbs, were relatively stable over the study period, with 99%, 96% and 90% of samples, respectively, having responses over baseline 4–8 months post‐infection. Anti‐RBD antibodies were strongly correlated with NAbs at all time points (Pearson's r ≥ 0.87), and feasibility of using finger prick sampling to accurately measure anti‐RBD IgG was demonstrated. Conclusion: Antibodies to SARS‐CoV‐2 persist for up to 8 months following mild‐to‐moderate infection. This robust response can be attributed to the initial exposure without immune boosting given the lack of community transmission in our setting. Abstract : This study shows that antibodies to SARS‐CoV‐2 persist for up to 8 months following mild‐to‐moderate infection. This robust response can be attributed to the initial exposure without immune boosting given the lack of community transmission in New Zealand. The figure was created with BioRender.com .